1997
DOI: 10.1111/j.1553-2712.1997.tb03693.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Deep Venous Thrombosis Associated with Femoral Venous Catheterization

Abstract: Objective: To determine in adult medical patients the incidence of deep venous thrombosis (DVT) resulting from femora] venous catheterization (FVC).Methods: A prospective, observational study was performed at a 420‐bed community teaching hospital. Hep‐arin‐coated 7‐Fr 20‐cm femoral venous catheters were inserted unilaterally into a femoral vein. Each contra‐lateral leg served as a control site. Age, gender, number of FVC days. DVT risk factors, administration of DVT prophylaxis, and DVT formation and site were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Interestingly, there are multiple reviews in the pediatric and adult literature citing an increased DVT rate with femoral catheters [6,[23][24][25][26][27][28][29][30]. In studies that separate patients by age, smaller patients (b1 year old) are found to have a higher incidence of femoral CVC-associated DVTs than any other group [5,6].…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, there are multiple reviews in the pediatric and adult literature citing an increased DVT rate with femoral catheters [6,[23][24][25][26][27][28][29][30]. In studies that separate patients by age, smaller patients (b1 year old) are found to have a higher incidence of femoral CVC-associated DVTs than any other group [5,6].…”
Section: Discussionmentioning
confidence: 93%
“…All reported bleeding complications DVT rates reported for patients hospitalized for acute stroke. 15,16 In the 1 patient who received hypothermia for ϳ1 hour (a 73-year-old man with a known history of coronary artery disease), intermittent supraventricular tachycardia (SVT) was reported as an adverse event beginning close to the initiation of cooling. This patient became agitated after administration of fentanyl and midazolam in preparation for catheter placement, which prompted his wife to withdraw study consent after only 67 minutes of cooling and may have contributed to his SVT.…”
Section: Resultsmentioning
confidence: 99%
“…The femoropopliteal venous system is most commonly involved. 11,14,18 These children are generally older and healthier at the time of admission than their counterparts with DVT acquired while in the hospital. These children are admitted and with treatment are rapidly discharged.…”
Section: Discussionmentioning
confidence: 98%